Exploring factors associated with environmental menaces in a typical Nigerian city: challenges to sustainable development (2012)
Creating and maintaining a sustainable environment remain one of the most pressing issues in the world today. Human settlements are confronted with the challenges such as the fall out of climate change, natural disasters such as flooding, diseases outbreak resulting from improper waste disposal, poor environmental sanitation and various degrees of human and economic crises. Overtimes, however, activities of man coupled with some ecological factors have become a very critical threat to the achievement of a sustainable environment. In this study, we presented an elucidating analysis and reports of some factors associated with the prevailing environmental challenges in Mowe, Ogun state, Nigeria. The possible causes, effects and lasting solutions to these problems were also presented. Detailed statistical analysis of the interrelationships between variables of interest was also carried out. Our results show that, of the 200 participants in the study, 106(53.0%) uses their backyard or compound as dump hills while 42(21.0%) uses the community dumps hills. Also, 159(79.5%) of buildings have septic/soak away systems while 23(11.5%) of them use open gutter and 11(5.5%) of the buildings have no sewage disposal systems at all. Results of the Multiple Logistic Regression show those who have drainages around their houses were more likely to be those who use backyard/community dump hills for sewage disposal, while those who use open Gutter and those with no defined sewage disposal system were more likely (than those who use the methods of sewage disposal) to perceive neglect of their area by the government